Changes in Tear Cytokine Concentrations Following Discontinuation of Soft Contact Lenses—A Pilot Study. Issue 4 (July 2016) - Chao, Cecilia; Golebiowski, Blanka; Stapleton, Fiona; Richdale, Kathryn
Abstract : Purpose: This study investigated changes in selected tear cytokine concentrations (IL-1β, IL-1Ra, IL-6, IL-10, IL-12 (p70), and TNF-α) after a 1-week washout from soft contact lens wear (CLW), and the repeatability of cytokine measurements using custom multiplex assays. Methods: A total of 10 subjects completed this 6-visit (immediately following contact lens removal, and after 1, 2, 3, 4, and 7 [±1] days without CLW) pilot study. Approximately 20 to 30 μL of pooled basal tears were collected from both eyes at each visit. Two custom multiplex assays were used by two operators to quantify the concentration of tear cytokines. Tear samples from subjects 1 to 6 were analyzed using the first kit by operator 1. Tear samples from subject 7 to 10 plus additional tear samples from subjects 1 to 5, which were used to determine the between-kit per operator repeatability, were analyzed using the second kit by operator 2. Linear mixed models were used to determine changes in tear cytokine concentrations over time. Between-kit per operator and within-kit per operator repeatabilities were assessed using the Bland and Altman analysis. Results: There were no significant changes in tear cytokine concentrations over a 1-week washout of CLW. More than 99% of the tear samples had detectable levels of cytokines using custom multiplex assays. Within-kit per operator repeatability was good, but between-kit per operator repeatability was poor; likely due to protein degradation, differences in operator experience, and operating procedures. Conclusion: A washout period may not be necessary when evaluating changes in tear cytokines with new contact lenses or lens care products. A well-trained operator using standardized operating procedures can produce repeatable measurements using custom multiplex assays.